Study of the self-stabilization ability of Tzatziki (a traditional Greek ready-to-eat deli salad) - Stavros Lalas; Vassilis Athanasiadis; Ioanna Karageorgou; Eleni Bozinou; Vassilis G. Dourtoglou (International Journal of Food Studies)
Traditional Greek yogurt-based salad Tzatziki is one of the most popular ready-to-eat deli salads in Greece. The objective of this study was to estimate the microbial stability of Tzatziki, with and without chemical preservatives, using a rapid method. Determination of the microbial count was carried out using the bioluminescence method (ATP) and traditional microbiological analysis, plate-counting method (CFU) in various batches of the final product of Tzatziki. The results showed that the Tzatziki salad without preservatives initially gave higher relative light units (RLU) values (79,532) than the same salad with preservatives (43,198) because the potassium sorbate and the sodium benzoate, used the in recipe, appeared to suspend the action of microorganisms. After incubation in two different substrates, MacConkey and Sabouraud, the Tzatziki salad without preservatives gave higher RLU values (9,488 and 16,176, respectively) than the salad with preservatives (12,780 and 12,005, respectively). In the two selective substrates, differences appeared between the two methods of microbial count (RLU and CFU). While RLU values were roughly at the same level, the CFU values presented significant differences (p < 0.05). It was also shown that there was a strong correlation (R 2 = 0.93-0.95) between bacterial counts estimated by traditional CFU and ATP methods. As expected, the dominant microbial population in Tzatziki was Lactobacillus spp., originated from yogurt. Coliforms and yeasts were not able to survive in this environment. Generally, according to the results, Greek traditional Tzatziki salad was a microbial stable product and the bioluminescence method could be a rapid method to determine its microbial state.